ANTIBACTERIAL EFFECT OF GLASS IONOMER AND ZINC OXIDE CHKM CEMENT AS ROOT CANAL FILLER TOWARD STREPTOCOCCUS VIRIDANS: EFEK ANTIBAKTERI SEMEN IONOMER KACA DAN ZINK OKSID CHKM SEBAGAI BAHAN PENGISI SALURAN AKAR TERHADAP STREPTOCOCCUS VIRIDANS - Dwi Warna Aju Fatmawati; Ekiyantini Widowati (Dentika: Dental Journal, 2011)
Luting type glass ionomer cement (GIC) can be used as root canal filler. Because GIC has biocompatiblity and contained fluor, clinicians used zinc oxide ChKM (ZnOChKM) as root canal filler that contained parachorophenol, camper, and menthol. ChKM has a ability as wide spectrum antibacterial and low irritation. The Aim of study was to know antibacterial of luting type glass ionomer and zinc oxide ChKM as root canal filler toward Streptococcus viridans. This study was a laboratory experimental, contained of 7 samples of luting type GIC and 7 samples ZnOChKM cement. The characteristics were 2 mm of the thickness and 5 mm of diameter, non porous, homogen, and smooth. Each sample was taken in TSA medium that had been inoculated Streptococcus viridans. TSA medium was perforated by straw like the samples size. After samples were incubated for 1, 7, and 14 days, we measured inhibition zone around samples by caliper. All data was analyzed by T – test (α=0.05). The result showed that mean of ZnOChKM cement inhibition zone cement on the first day was 2.12 cm; seventh days was 2.46 cm; and 14th days was 2.86 cm. Mean of GIC inhibition zone on the first day was 0.46 cm; seventh days was 1.18 cm; and 14th days was 1.26 cm. ZnOChKM cement zone inhibition was large than GIC inhibition zone. T – test analysis showed there was significant different between ZnOChKM cement and luting type GIC in all observation time. In conclusion, ZnOChKM cement as a root canal filler was more effective than GIC to inhibit growth of Streptococcus viridans.